An Implementation of Coding and Indexing Application for Outgoing Patients at Puskesmas Bringkoning Madura - ., Wincoko; Mahmud, Muhamad; Kurniasari, Iin (KnE Social Sciences, 2023)
Community health centers (Pusat Kesehatan Masyarakat - Puskesmas) must provide fast and appropriate health services. Regarding this role, Puskesmas Bringkoning Madura has developed a web-based outpatient coding and indexing system to provide the immediate service the patients need. The web-based application was created using the waterfall model method with the PHP and MySQL programming languages. This study aimed to describe the implementation of the coding and indexing application system for outpatients. The study employed a positivistic quantitative approach. The survey was conducted on medical record personnel, medical officers, and doctors as implementers of the outpatient coding and indexing application with 3 (three) indicators. Almost all respondents indicated that the outpatient coding and Indexing Application helped much in supporting the work of outpatient services. Keywords: indexing, application, outgoing patients